2008
DOI: 10.1007/s11099-008-0070-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the interaction between ozone and carbon dioxide on gas exchange, ascorbic acid content, and visible leaf symptoms in rice leaves

Abstract: Tropospheric ozone (O 3 ) decreases photosynthesis, growth, and yield of crop plants, while elevated carbon dioxide (CO 2 ) has the opposite effect. The net photosynthetic rate (P N ), dark respiration rate (R D ), and ascorbic acid content of rice leaves were examined under combinations of O 3 (0, 0.1, or 0.3 cm 3 m -3 , expressed as O 0 , O 0.1 , O 0.3 , respectively) and CO 2 (400 or 800 cm 3 m -3 , expressed as C 400 or C 800 , respectively). The P N declined immediately after O 3 fumigation, and was large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
16
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 44 publications
(48 reference statements)
9
16
0
Order By: Relevance
“…Similarly, the combination of Chi+EO 3 70 helped to reduce the effect of elevated ozone, whilst they were significantly higher than the sample under EO 3 70. Imai and Kobori (2008) found that shoot, root and total biomass yields of rice were decreased by elevated ozone that suppressed photosynthesis. Rice was considered as another sensitive crop, similar to wheat, which showed reduction of biomass even when exposed to mild ozone concentration at 40 ppb (Feng et al, 2008).…”
Section: The Effect Of Chitosan On Biomass Under Elevated Ozonementioning
confidence: 99%
“…Similarly, the combination of Chi+EO 3 70 helped to reduce the effect of elevated ozone, whilst they were significantly higher than the sample under EO 3 70. Imai and Kobori (2008) found that shoot, root and total biomass yields of rice were decreased by elevated ozone that suppressed photosynthesis. Rice was considered as another sensitive crop, similar to wheat, which showed reduction of biomass even when exposed to mild ozone concentration at 40 ppb (Feng et al, 2008).…”
Section: The Effect Of Chitosan On Biomass Under Elevated Ozonementioning
confidence: 99%
“…The RDS of ascorbic acid in the flag leaf was slightly higher than that in other positioned leaves (not significant at P ≤ 0.05, but significant at P ≤ 0.10). Imai and Kobori (2008) reported that the inhibition of P N in rice leaves by short exposure to O 3 was explained considerably by decreased g s , and at a high O 3 ) of total, reduced form (AA) and oxidized form (DHA) of ascorbic acid and its redox state (RDS) in the 16th (flag leaf) − 13th leaves. In each column, means (n = 4) followed by the same letter are not significantly different at P ≤ 0.05 level as inferred from results of one-way ANOVA.…”
Section: Ascorbic Acid Contents In Different Leaf Positionsmentioning
confidence: 99%
“…Therefore, the effects of exposure to O 3 on physiological processes of rice need to be studied as a basis of dry matter production and yield formation. When exposed to O 3 , rice plants suffer damage such as the inhibition of net photosynthetic rate (P N ), stomatal conductance to CO 2 transfer (g s ), photosystem II (PSII) (Imai and Kobori, 2008;Kobayakawa and Imai, 2011a), decreased ribulose 1,5-bisphosphate carboxylase / oxygenase (Ishioh and Imai, 2005), chlorophyll and carotenoid Rai and Agrawal, 2008) contents and nitrite reductase activity (Kobayakawa and Imai, 2011b), in addition to breakdown of the cellular ultrastructure (Toyama et al, 1989) and visible leaf-related symptoms (Imai and Kobori, 2008). Furthermore, O 3 suppresses the growth rate (Imai and Ookoshi, 2011), alters photoassimilate partitioning (Nouchi et al, 1995) and ultimately decreases the grain yield (Reid and Fiscus, 2008;Yamaguchi et al, 2008;Pang et al, 2009;Rai et al, 2010;Imai and Ookoshi, 2011).…”
mentioning
confidence: 99%
“…Of photochemical oxidant components, 90% or more are O 3 (Cabrera et al, 1988;Nouchi, 2001). When exposed to O 3 , rice plants suffer damage: inhibition of net photosynthetic rate (P N ), stomatal conductance (g s ) and PSII (Imai and Kobori, 2008;Imai, 2011a, 2012a), decreased ribulose 1,5-bisphosphate carboxylase/oxygenase (Ishioh and Imai, 2005), chlorophyll and carotenoid (Rai and Agrawal, 2008) contents and nitrite reductase activity (Kobayakawa and Imai, 2011b), in addition to visible leafrelated symptoms (Imai and Kobori, 2008) and breakdown of the cellular ultrastructure (Toyama et al, 1989). By using a passive light microscope, the 3-D chlorophyll fluorescence imaging suggested that O 3 injury began just under the epidermal cells (Endo and Omasa, 2007).…”
mentioning
confidence: 99%
“…Under elevated CO 2 , the g s of plants generally decreases. Consequently, O 3 -inhibition decreases because of the limited inflow of O 3 through stomata (Booker and Fiscus, 2005;Imai and Kobori, 2008). In rice plants, O 3 -inhibition of photosynthesis is ameliorated by elevated CO 2 (Imai and Kobori, 2008;Imai, 2011a, 2012a).…”
mentioning
confidence: 99%